Global imbalances: The evolution of the process and policy responses - Ryszard Wilczyński (Contemporary Economics, 2008)
During the last ten years the global economy recorded strong growth with only mild and short slowdown at the early 2000's and with the another slowdown in 2007-2008. This growth was driven by the high dynamics of global demand, in excess of production capacities, and led to increasing tensions and disequilibrium such as asset bubbles, external imbalances and, ultimately, inflationary pressures and a turbulence on financial markets in 20072008. There are disagreements among economists and policy makers about the causes and implications of global imbalances. A sustainability view maintains that global financial markets provide a useful framework for a relatively smooth unwinding of global imbalances. A critical view emphasizes an overshooting by financial markets and the need for policy responses to global imbalances. The article argues in favor of the latterview and maintains that it is important to consider these imbalances linked to other market failure related risks to a sustainable growth of the global economy. Policy adjustments to global imbalances should be internationally coordinated. The effectiveness of policy responses to global imbalances will be enhanced if action is organized within the framework of a credible global financial institution.
Keywords: 330